1982
DOI: 10.1080/03014223.1982.10423848
|View full text |Cite
|
Sign up to set email alerts
|

The Phytoseiidae of New Zealand (Acarina) 1. The generaTyphlodromusandAmblyseius —keys and new species

Abstract: Keys are given to the 5 genera of the subfamily Phytoseiinae and to the 24 species of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…2). However, the record of N. longispinosus in New Zealand (Collyer, 1982) may be confusing because A. womersleyi was described as a synonym of A. longipinosus. From the information of habitat plants and geographic distribution of N. longispinosus in this study, we conclude that N. longispinosus has a high potential to survive at various areas and on a wide variety of habitat plants and this predator will play an important role in suppressing populations of spider mites in Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…2). However, the record of N. longispinosus in New Zealand (Collyer, 1982) may be confusing because A. womersleyi was described as a synonym of A. longipinosus. From the information of habitat plants and geographic distribution of N. longispinosus in this study, we conclude that N. longispinosus has a high potential to survive at various areas and on a wide variety of habitat plants and this predator will play an important role in suppressing populations of spider mites in Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…162), slightly more than half of L 4 in Garman (1958;fig. 5) and in specimens examined in this paper, and slightly less than half of L 4 in Collyer (1982). In should be noted that differences in the relative length of dorsal setae were used to differentiate species in some species-groups in this genus (e.g.…”
Section: Notes On Variation In Morphologymentioning
confidence: 99%
“…5) showed that M 2 is slightly longer than L 4 but slightly less than half as long as L 9 . Collyer (1982) described New Zealand specimens of A. perlongisetus, and accepted the broad concept of this species. She characterized these three long setae as "L 4 and M 2 are elongate ...... and L 9 is long and whiplike, twice as long as M 2 " in her description (p. 194) but as "L 4 and M 2 also long, more than half as long as L 9 " in her key to species (p. 187).…”
Section: Notes On Variation In Morphologymentioning
confidence: 99%
See 2 more Smart Citations